Estimation of Polymerization Rate Constants Using Experimental Residence Time Studies in Industrial Pilot Plant Equipment. Issue 4 (28th May 2018) - Karjala, Thomas W.; Kolthammer, Brian W. S.; Zhang, Min; Jain, Pradeep
Abstract: Estimation of polymerization rate constants is industrially important for reactor design, reactor control, and evaluation of the productivity and product properties of new catalyst systems. Propagation and catalyst deactivation rate constants are particularly important as they control how a given catalyst system will behave in a given reactor. Pilot scale reactors are used to investigate the kinetics of solution ethylene polymerization of several catalyst systems; a heterogeneous Ziegler–Natta (Ti/MgCl2 ) and two constrained‐geometry molecular catalysts. A model is developed to estimate the propagation and first order catalyst deactivation rate constants through carefully conducted residence time experiments. D‐optimal experimental design criteria is used to determine the appropriate experimental conditions. Analysis shows that the observed propagation rate constant is confounded by catalyst poisons while the catalyst deactivation rate constant is independent of these factors. This helps explain how to obtain significantly larger propagation rate constants than have been previously reported in the literature. Abstract : Continuous, pilot plant scale, residence time experiments are used to estimate propagation and catalyst deactivation rate constants for several industrially important catalysts. Significantly larger propagation rate constants are obtained compared to previously reported values in the literature.